Local checkpoint inhibition of CTLA‐4 as a monotherapy or in combination with anti‐PD1 prevents the growth of murine bladder cancer. Issue 2 (13th December 2016) - van Hooren, Luuk; Sandin, Linda C.; Moskalev, Igor; Ellmark, Peter; Dimberg, Anna; Black, Peter; Tötterman, Thomas H.; Mangsbo, Sara M.
Abstract : Local low‐dose administration of anti‐CTLA‐4 effectively restrains s.c. Murine bladder 49 (MB49) tumor growth and decreases circulating antibody levels. Intratumoral (i.t.) injection into orthotopically growing bladder tumors further decreases circulating antibody levels more than tenfold. Application of s.c. or i.t. low‐dose anti‐CTLA‐4 should therefore be investigated as a clinical delivery strategy to reduce adverse events associated with CTLA‐4 checkpoint blockade. Abstract : Checkpoint blockade of CTLA‐4 results in long‐lasting survival benefits in metastatic cancer patients. However, patients treated with CTLA‐4 blockade have suffered from immune‐related adverse events, most likely due to the breadth of the induced T‐cell activation. Here, we investigated the efficacy of a local low‐dose anti‐CTLA‐4 administration for treatment of subcutaneous or orthotopic murine bladder 49 (MB49) bladder carcinoma in C57BL/6 mice. When MB49 tumors were grown s.c., peritumoral (p.t.) injection of anti‐CTLA‐4 treatment was equally effective as intravenous or s.c. (nontumor bearing flank) administration. Notably, p.t. injection was associated with lower circulating antibody levels and decreased IL‐6 serum levels as compared to systemic treatment. Ultrasound‐guided intratumoral anti‐CTLA‐4 antibody treatment of orthotopically growing MB49 tumors resulted in tumor regression, with more than tenfold reduction in systemic antibody levels as compared to i.v. or s.c. administration, in line with the compartmentally restrained nature of the bladder. Local anti‐CTLA‐4 therapy in combination with anti‐PD‐1 therapy resulted in complete responses, superior to each therapy alone. In addition, p.t. anti‐CTLA‐4 therapy was potentiated by depletion of regulatory T cells. Our results demonstrate that local anti‐CTLA‐4 antibody therapy is equally effective as systemic administration, but reduces systemic antibody levels and cytokine release, and enhances the response to anti‐PD1 therapy.